(untitled) (CIPEEX, 2025)
Cardiopulmonary diseases, such as myocardial infarction, heart failure, and chronic obstructive pulmonary disease (COPD), represent significant causes of mortality in Brazil. These conditions mainly affect adults and the elderly, with risk factors such as physical inactivity, smoking, and hypertension. To analyze mortality from cardiopulmonary diseases in Brazil and in Goiás, focusing on the municipalities of Carmo do Rio Verde, Ceres, and Rialma in 2023. This is a retrospective descriptive analysis conducted using data from the Mortality Information System (SIM/DATASUS), as well as updated municipal records through 2023. In 2023, cardiovascular diseases were the leading cause of death in Brazil, with more than 400,000 deaths, followed by respiratory diseases such as COPD and pneumonia. In Goiás, according to DataSUS, the municipalities of Ceres, Rialma, and Carmo do Rio Verde recorded, respectively, 44, 39, and 23 deaths from these causes. The main associated conditions were acute myocardial infarction, heart failure, hypertension, and COPD. Ceres presented a higher incidence of pneumonia and chronic pulmonary diseases, while Carmo do Rio Verde and Rialma stood out for the high prevalence of infarction and heart failure. Cardiopulmonary diseases remain a major challenge for public health. Preventive actions, health education, and the expansion of primary care are essential to reduce mortality and improve the population’s quality of life.